The Influence Of Management Information Systems On Organizational Performance: A Systematic Literature Study - Fahriana, Nahdia Neily (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
In today's digital era, management information systems play a role in helping organizations work faster, more precisely, and more efficiently. This study analyzes the impact of management information system implementation on organizational performance through a systematic review of 30 literature studies. The results show that management information systems significantly impact organizational performance. However, the effectiveness of management information systems depends not only on technology but also on system integration, data quality, and the organization's readiness to adopt digital innovation. This review identified a research gap, particularly the need to examine the impact of management information systems across sectors and combine quantitative and qualitative methods to understand the factors that hinder implementation. This study highlights the need for an implementation strategy.management information systemcomprehensive approach to improve organizational performance across various sectors.